The Lip Length and Thickness in Relation to Smile Line - Alqaysi, Shadha; Al-Demirchi, Jehan Yawez; Qasim, Tabark (Journal of Science in Medicine and Life, 2024)
Background: The smile plays an important role in personal, professional, and romantic relationships among humans. The aesthetic of smile depends on the relationship between the teeth and lips and the way that lips and soft tissue frame the smile. Method: The study was conducted in the department of dentistry, of Al-Hadi University College in Baghdad. 240 subjects (120 males and 120 females) were examined in this study whose age ranged from 18 to 30 years. We used vernier caliper for the measurement of the upper lip length, upper lip thickness and smile line. Results: There were high statistically significant gender differences observed for lip length and lip thickness with males than females (There were significant differences in smile line scores with the mean score for males (M= - 0.04) was lower than females (M= + 2.95). Conclusion: There was significant positive correlation between (upper lip length at rest and upper lip thickness) and smile line among Iraqi students. There is also a significant difference between males and females in upper lip length, upper lip thickness and smile line among Iraqi students.